Assessing the long-term implications of age 9 initiation of HPV vaccination on series completion by age 13–15 in the US: projections from an age-structured vaccination model - Saxena, Kunal; Patterson-Lomba, Oscar; Gomez-Lievano, Andres; Zion, Abigail; Cunningham-Erves, Jennifer; Kepka, Deanna (Frontiers in Pediatrics, 2024)
Routine human papillomavirus (HPV) vaccination in the US is recommended at ages 11 or 12 years and can be given at age 9. Vaccination completion rates among adolescents 13-15 years in the US remain below the 80% goal. This study evaluated the long-term effects of increasing proactive HPV vaccination initiation rates at age 9 years in completion rates of adolescents. An age-structured vaccination model was developed and parametrized based on the National Immunization Survey-Teen (NIS-Teen) survey data. The model projected vaccination coverage (by vaccination status and age group), for 20 years, for a routine initiation scenario (no increase in initiation rates of 9-year-olds) and different proactive initiation (increased age 9 initiation) scenarios. The time to reach a completion rate of 80% for 13-15-year-olds was estimated. The model also generated projections stratified for subgroups of interest. Results indicated that vaccine completion rates of 80% in 13-15-year-olds may not be achieved by 2040 under current trends of routine initiation at ages 11 or 12 years. However, increasing initiation rates in 9-yearolds by 1% and 3% annually could shorten the time to achieve 80% completion by 4 and 8 years, respectively. Stratification analyses showed that increasing initiation rates in 9-year-olds can also reduce disparities across subgroups in the time to achieve vaccination completion targets.Increasing HPV vaccination initiation rates in 9-year-olds by as little as 1-3% annually may be an effective strategy to improve HPV vaccination completion rates in adolescents by age 15 and reach the Healthy People goal of 80% completion much earlier.